Placing transdisciplinarity in context: a review of approaches to connect scholars, society and action - Knapp, Corrine Nöel, author; Reid, Robin S., author; Fernández-Giménez, María E., author; Klein, Julia A., author; Galvin, Kathleen A., author; MDPI, publisher (Colorado State University. Libraries, 2019)
Complex sustainability problems (e.g., climate change) are challenging to understand and manage, leading to an increase in approaches that connect scholars to society and research to action (collaborative approaches). The transdisciplinary approach (TDA) represents one such approach. While TDA is new to many, there are several prior collaborative approaches including collaborative adaptive management, knowledge integration, participatory action research, and indigenous/local knowledge. Other contemporary and parallel approaches include citizen science, translational science, evidence-based practice, and knowledge with action. The varied disciplinary roots and problem areas contribute to a lack of interaction among these parallel but distinct approaches, and among the scholars and stakeholders who practice them. In this paper, we consider the connections, complementarities and contradictions among these distinct but related collaborative approaches. This review offers insights into the interaction between science and practice, including the importance of social processes and recognition of different ways of knowing, as well as how to conduct collaborative approaches on a variety of scales and think about how to generalize findings. The review suggests a need to rethink roles and relationships in the process of knowledge co-creation, both extending the roles of researchers and practitioners, creating new hybrid roles for "pracademics", and placing greater awareness on issues of power.
Keywords: transdisciplinary; co-production; antecedents; knowledge integration; participatory action research; Indigenous knowledge; local knowledge; citizen science; translational science; evidence-based practice; knowledge with action